PENERAPAN PROBLEM-BASED LEARNING BERBASIS PERMAINAN “ULAR TANGGA” DALAM MENINGKATKAN PEMAHAMAN MATEMATIS PESERTA DIDIK SEKOLAH DASAR DI KOTA BANDUNG - Dini Nurhidayah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is undermined by the fact that the level of mathematical understanding in class 3B SDN 096 Sarijadi Selatan, Bandung for the academic year 2022/2023 is still low and, in particular, has not properly understood the concept of the materials taught. The use of the problem-based learning (PBL) model packed into the game of thematic snake staircase (ULTAMET) becomes one of the options to enhance the mathematical understanding of the learners. Problem-based learning, packed into the game of snake staircase," is learning that focuses on fun problem-solving activities. The purpose of this action research in general is to improve the quality of the learning process in the classroom, and the aim of this action research is to know how problem-based learning based on the game Snake Staircase can improve the mathematical understanding of students in class 3B SDN 096 Sarijadi Selatan. This class action study uses Kemmis and McTaggart designs that have four stages in the implementation of class action research: planning, action, observation, and reflection. The instruments used include mathematical understanding tests and guidelines for the observation of student learning activities. Based on the results of the action of three cycles, it was shown that: 1) the problem-based learning model based on the game of snake stairs can improve the understanding of students of class 3B SDN 096 Sarijadi Selatan; 2) on the basis of the N-gain test results, the improvement in the mathematical understanding of learners by 83.13% was effectively interpreted, and the learning activity of students continued to improve in each cycle and reached 86% with excellent categories. Based on the findings of this study, it was concluded that the mathematical understanding of students in class 3B SDN 096 Sarijadi Selatan increased after learning using a problem-based learning model based on a game of snake stairs.